2D Chemistry: Chemical Control of Graphene Derivatization - Matochová, Dagmar; Medved', Miroslav; Bakandritsos, Aristides; Steklý, Tomáš; Zbořil, Radek; Otyepka, Michal (The journal of physical chemistry letters, 2018)
Controllable synthesis of graphene derivatives with defined composition and properties represents the holy grail of graphene chemistry, especially in view of the low reactivity of graphene. Recent progress in fluorographene (FG) chemistry has opened up new routes for synthesizing a plethora of graphene derivatives with widely applicable properties, but they are often difficult to control. We explored nucleophilic substitution on FG combining density functional theory calculations with experiments to achieve accurate control over the functionalization process. In-depth analysis revealed the complexity of the reaction and identified basic rules for controlling the 2D chemistry. Their application, that is, choice of solvent and reaction time, enabled facile control over the reaction of FG with N-octylamine to form graphene derivatives with tailored content of the alkylamine functional group (2.5-7.5% N atomic content) and F atoms (31.5-3.5% F atomic content). This work substantially extends prospects for the controlled covalent functionalization of graphene.